Relationship between pest birds and landscape elements in the Pampas of Central Argentina - Codesido, Mariano (2015)
Many species of birds are considered pests in rural areas modified for agricultural production. We evaluated the abundance of four species of avian pests (Eared Dove (Zenaida auriculata), Monk Parakeet (Myiopsitta monachus), Picazuro Pigeon (Patagioenas picazuro) and Spot-winged Pigeon (P. maculosa)) in the Pampas of central Argentina. From 2006 to 2008, we surveyed 35 transects along secondary roads. All four species showed a response to the presence of exotic woodlots in rural areas. Monk Parakeets and the two pigeons were more likely to be found in woodlots with tall, perennial trees (Eucalyptus spp.), whereas Eared Doves were more likely to be found in woodlots with short, perennial trees (mainly species of Pinus and Casuarina). We did not detect any association between abundance of pest species and the presence of crops. These results suggest that management of exotic perennial trees in rural areas of the Pampas of central Argentina may provide a means of control of pest birds.